2016
DOI: 10.1093/heapro/daw084
|View full text |Cite
|
Sign up to set email alerts
|

Just a subtle difference? Findings from a systematic review on definitions of nutrition literacy and food literacy

Abstract: Nutrition literacy and food literacy have become increasingly important concepts in health promotion. Researchers use one or the other term to describe the competencies needed to maintain a healthy diet. This systematic review examines whether these terms are synonymous or if their meanings are substantially different.We searched major bibliographic databases (Web of Science, PubMed, ScienceDirect, CINAHL, SocIndex and ERIC) for publications that provided an original definition of nutrition or food literacy. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
249
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(306 citation statements)
references
References 39 publications
1
249
0
25
Order By: Relevance
“…The proposed systematic review and meta-analysis will be conducted following the guidance in the Cochrane Collaboration Handbook of Systematic Reviews [34]. The methods and results will be reported in accordance with the reporting guidance provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [35].…”
Section: Methodsmentioning
confidence: 99%
“…The proposed systematic review and meta-analysis will be conducted following the guidance in the Cochrane Collaboration Handbook of Systematic Reviews [34]. The methods and results will be reported in accordance with the reporting guidance provided in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [35].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies showed that FL can be interpreted as a specific form of health literacy [47], which was theorized by the Nutbeam's model as being characterized by three levels as functional, interactive and critical [48]. The lowest functional level includes basic reading and writing skills necessary to understand and follow simple nutrition messages; the interactive level includes the skill of sharing nutritional information with others to promote healthy eating pattern; the critical level is the ability to analyze nutrition information critically, increase awareness, and participate in action to address barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Articles were found using terms like food literacy, nutrition literacy or functional literacy, interactive literacy, critical literacy (all applied to nutrition), and health literacy, apparently referring to similar issues. 25,32,41 Two food and nutrition literacy questionnaires validated for Portuguese population were found, 42,43 but required a high baseline literacy by the target population. Those questionnaires were focused, respectively, on labels reading and calculation 38 ; and nutrition topics like antioxidants, micronutrients, and nutritional therapy for diseases 39 ; as the Nutriscience Project aimed to reach the whole spectrum of social socioeconomic status, these questionnaires were not appropriate.…”
Section: Discussionmentioning
confidence: 99%